Maintenance management of convention centres / Norashikin Akhiar @ Khairuddin - Akhiar @ Khairuddin, Norashikin (Faculty of Architecture, Planning and Surveying, 2010)
Convention centre is one of the buildings and facility that should well function and need to be organized a proper maintenance management through their planning, organization, manual, budget, standard and strategy. Maintenance management is important to be taken into consideration in order to protect the asset which consists of building, equipment and support facilities from defects and damages. It has lot of advantages in maintaining the particular asset such as convention centre. The organization of convention centre should protect the value of the building, equipment and a facility with a good maintenance management as it is the key sources of investment beside the return on the profit that definitely will be obtained if the convention centre can function well without any serious defect occurred. To retain the function is another benefit besides the good appearance of the convention centre itself. Problem will occur if the maintenance aspect is neglected as the main reason of doing maintenance is the safety. If the building and equipment is defected, broken and damages, it will probably dangerous and being uncomfortable to occupants and visitors. After all, convention centre should be in a safe condition and comfortable place as well. In looking to the importance of the maintenance for the convention centre, a research will be conducted on the Maintenance Management of Convention Centres.